Cytarabine ears – A side effect of cytarabine therapy. (March 2020) - Doval, Divya; Kumar Sharma, Sanjeev; Kumar, Meet; Khandelwal, Vipin; Choudhary, Dharma
Cytarabine, a pyramidine analog, is used for treating various hematological malignancies such as acute leukemias and lymphomas. Side effects of cytarabine are dose dependent and include bone marrow suppression, fever, cerebellar toxicity, cardiomyopathy, hepato-renal insufficiency, necrotizing enterocolitis, pancreatitis, acute respiratory distress, corneal toxicity and dermatological side effects. The dermatological side effects can be immediate or due to delayed hypersensitivity reactions. They have been attributed largely to release of cytokines. We present three such cases of delayed hypersensitivity to cytarabine affecting the ears bilaterally.